PERAN BADAN USAHA MILIK DESA (BUMDES) BANGUN GLOBAL PRESTASI DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI DESA BURANGKENG KECAMATAN SETU KABUPATEN BEKASI - Wanda Yusriyah; Sudadio Sudadio; Ino Sutrisno Rawita (Jurnal Abdimas Bina Bangsa, 2024)
Community empowerment is one way to make big changes for rural communities. Empowerment is carried out to create an independent society. A Village-Owned Enterprise (BUMDes) is a village economic institution managed by the community and village government whose aim is to improve community welfare, and to improve the community's standard of living through the economy. This research was conducted to reveal (1) What is the role of Village-Owned Enterprises (BUMDes) in improving the welfare of the people of Burangkeng Village, Setu District, Bekasi Regency, (2) What are the results of Village-Owned Enterprises (BUMDes) in improving the welfare of the people of Burangkeng Village, Setu District, Bekasi Regency , (3) What factors support and hinder the running of Village-Owned Enterprises (BUMDes) in improving the welfare of the people of Burangkeng Village, Setu District, Bekasi Regency. This research uses a qualitative approach with descriptive methods. The data collection techniques used were observation, interviews and documentation. The data sources in this research were obtained from 7 informants consisting of 1 Village Head, 1 Village Secretary, 1 Director of BUMDes Bangun Global Prestasi, 2 business actors in BUMDes, and 2 village residents. The research results explain that BUMDes Bangun Global Prestasi in Burangkeng Village is a village business institution that plays a role in facilitating economic activities, marketing community products, and empowering the community. The role of BUMDes Bangun Global Prestasi can be said to be quite instrumental in improving the welfare of village communities, but it is not optimal because there is still inequality of welfare between village communities. This is due to the many obstacles, namely lack of capital and even budget constraints, human resources for managing BUMDes are still lacking, and the socialization carried out is still uneven